Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1080/13698571003637048
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain futures: Individual risk and social context in decision-making in cancer screening

Abstract: A core logic of cancer control and prevention, like much in public health, turns on the notion of decision-making under conditions of uncertainty. Population-level data are increasingly used to develop risk profiles, or estimates, that clinicians and the consumer public may use to guide individual decisions about cancer screening. Individual risk perception forms a piece of a larger social economy of decision-making and choice that makes population screening possible. Individual decision-making depends on acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 61 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…Additionally, in the Limuru study, women frequently had misconceptions about cervical cancer risk factors and said that they did not feel the need for screening because they felt healthy [7]. Perceptions of risk are formed by information, emotional experiences, and cultural frameworks within a community; and studies have suggested that perception of personal risk for developing cancer can affect cancer screening behaviors [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the Limuru study, women frequently had misconceptions about cervical cancer risk factors and said that they did not feel the need for screening because they felt healthy [7]. Perceptions of risk are formed by information, emotional experiences, and cultural frameworks within a community; and studies have suggested that perception of personal risk for developing cancer can affect cancer screening behaviors [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Less restrictive research in cancer risk perception requires the development of novel measures that go beyond typical probability and severity judgments. It is critically important, as well, that these measures be developed and validated with input at the outset from diverse populations, since approaches to managing uncertainty in general (Hofstede, 2001), and the health risk perception process in particular, probably differ across cultures (Huerta and Macario, 1999, Francois et al ., 2009, Joseph et al ., 2009, Pasick et al ., 2009, Lee, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Conducting risk perception research with diverse populations is a critical step in understanding the diverse range of ways that deliberative and intuitive risk perceptions function in and across diverse cultures, that has the potential to shed light on how people manage uncertainty in general (Hofstede, 2001), and the health risk perception process in particular, probably differ across cultures (Francois et al, 2009; Huerta & Macario, 1999; Joseph et al, 2009; Lee, 2010; Pasick et al, 2009). We are currently conducting work validating Spanish and Haitian translations of intuitive risk perception measures (Hay, Brennessel, et al, 2014) and examining risk perception and patient activation across diverse language groups (Hay et al, 2015).…”
Section: Discussionmentioning
confidence: 99%